PARACETAMOL-RELATED TOXIC EVENTS TOXIC EVENTS ASSISTED BY A TOXICOLOGICAL INFORMATION AND ASSISTANCE CENTER: Eventos toxicológicos associados a paracetamol atendidos por um centro de informação e assistência toxicológica - Nascimento, Eduarda Carolina do; Guidoni, Camilo Molino; Girotto, Edmarlon (Revista de Ciências da Saúde Nova Esperança, 2024)
This study aimed to analyze the toxicological events associated with paracetamol managed by a Toxicological Information and Assistance Center. It was a cross-sectional, retrospective study based on cases of toxicological events associated with the drug paracetamol attended by the Toxicological Information and Assistance Center of Londrina (CIATox/Londrina). The data was extracted from the Brazilian Poison Data System (DATATOX) from 2017 to 2021. The data was analyzed using the Statistical Package for the Social Sciences (SPSS), version 19.0. This study was approved by the Research Ethics Committee of the State University of Londrina. Between 2017 and 2021, CIATox/Londrina received 685 cases of toxicological events associated with paracetamol, of which the vast majority (75.0%) were women who had attempted suicide (83.2%) as their main circumstance. Most cases (37.7%) occurred in the afternoon on Saturdays and Sundays, the days of the week with the highest number of cases (15.7% and 16.2%, respectively). Paracetamol was combined with other substances in 156 (22.8%) cases. Almost 80.0% of the cases had clinical manifestations, with 36.4% requiring hospitalization (minimum of one and maximum of 37 days). Most cases were categorized as mild (57.7%), and four (0.6%) deaths were identified among all the cases. The antidote N-acetylcysteine was administered to 37.1% (N=255) patients. In general, toxicological events associated with paracetamol occurred predominantly in women in the afternoon and on Saturdays and Sundays, and involved suicide attempts. It is, therefore, essential to develop campaigns that encourage the correct use of medication and other public health campaigns, especially for those individuals who are more susceptible to suicide attempts.